2006
DOI: 10.2134/jeq2004.0288
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Emissions from Swine Waste Lagoons in the Utah Great Basin

Abstract: In animal production systems (poultry, beef, and swine), current production, storage, and disposal techniques present a challenge to manage wastes to minimize the emissions of trace gases within relatively small geographical areas. Physical and chemical parameters were measured on primary and secondary lagoons on three different swine farming systems, three replicates each, in the Central Great Basin of the United States to determine ammonia (NH3) emissions. Nutrient concentrations, lagoon water temperature, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…In 2004, a biofuel treatment system was constructed at an existing facility in the semiarid U.S. Central Great Basin. The emissions from this farm system had previously been measured during 2000–2001 (Harper et al, 2006), so this was an ideal location to compare the effects of treatment for conversion of manure to biofuels (on gas emissions) with the previously measured gas emissions. In addition to this study, a concurrent short‐term study was conducted onsite using different measurement technology (Harper et al, 2010).…”
mentioning
confidence: 99%
“…In 2004, a biofuel treatment system was constructed at an existing facility in the semiarid U.S. Central Great Basin. The emissions from this farm system had previously been measured during 2000–2001 (Harper et al, 2006), so this was an ideal location to compare the effects of treatment for conversion of manure to biofuels (on gas emissions) with the previously measured gas emissions. In addition to this study, a concurrent short‐term study was conducted onsite using different measurement technology (Harper et al, 2010).…”
mentioning
confidence: 99%
“…Harper et al (2004) found in a highly measured swine production operation that about 5% of the N going into the operation as feed left the lagoon as volatile NH 3 and another 1% from field application of waste effluent. Much of the N (about 43% of input feed) that entered into lagoons was found to be denitrified to N 2 (Harper and Sharpe, 1998; Harper et al, 2000, 2004) by microbial and/or chemical (Van Cleemput, 1998) denitrification. Another source of NH 3 emissions that has not been comprehensively measured is emissions from animal production houses.…”
mentioning
confidence: 99%
“…, nitrate (NO 3 -), nitrite (NO 2 -), and pH (for a description of analysis procedures see Harper et al 2000Harper et al , 2006. All lagoons were sampled similarly on a monthly basis.…”
Section: Methodsmentioning
confidence: 99%
“…From a systems' analysis approach using the USEPA National Emissions Inventory (USEPA, 2004), the addition of all NH 3 emissions' components, such as from housing (22 %), lagoons (43 %), field application of manure (23 %), N leaving as animal protein (30 %, from host data), suggest that more than 100 % of the N entering the farm system is leaving the farm as NH 3 volatilization plus animal product. Recent studies in North Carolina (NC) (Harper et al 2004b), the Georgia Coastal Plains (GA) (Harper and Sharpe 1998;Harper et al 2000), and the Central Great Basin (CGB) (Harper et al 2010;Weaver et al 2012) regions have shown that swine lagoons emit significantly less NH 3 than previously and currently thought. Much of the N estimated as NH 3 gas emissions has been found to be converted to dinitrogen gas (N 2 ) (Harper et al 2000(Harper et al , 2004bWeaver et al 2012), representing an even larger discrepancy for the N balance of farm systems suggested by the USEPA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation